A Bibliometric Analysis on Motivation Between 2016 and 2020 of Physical Education in Scopus Database - Chen, Chi-Jung; Lee, Hung-Ying; Lin, Ren-Jie; Farng, Jenn-Kuen (Frontiers in Education, 2022)
Purpose: In the field of Physical Education (PE), which encompasses a wide range of variables, the question of motivation has become increasingly important. The bibliometric methods can help researchers and educators understand the related research of motivation. The purpose of this study was to explore the bibliometric characteristics of motivation in the field of PE from 2016 to 2020 that try to discover the related research context and topics. Methods: By using the keywords “motivation” and “physical education”, the bibliographic records and references have been retrieved from the Scopus databases (date of search: September 7, 2021). The Vosviewr software tool and Bibliometrix R package were used for information analysis and visualization. The themes include the annual publication, countries, journals, authors, co-occurrences, and theme trends. Finally, it is presented with the characteristics of the big picture of bibliometrics. Results: From the analysis of the above theme, this study showed that there were 623 studies published over the five years, with the number gradually increasing in 2017 and peaking in 2020. The number of citations was the highest in 2016. In terms of total publications, Spain, the United States, and Australia are the top three countries. Most of the articles were published in sport pedagogy and public health relevant journals. The four main research directions were identified: Education, activity, health, and self-determination theory. Conclusion: This study helped us to comprehend the consistent publishing and rapid development of motivation in PE research. Via the bibliometric analysis, we can also incorporate previous research and predicted trends. All these works can help us to understand the basic psychological needs, leadership styles, and teacher support of PE teachers, and the intrinsic and extrinsic motivations of students at different ages. It is suggested that the in-depth study could be conducted on a single variable or emerging issues for future investigation. Researchers can keep tracking and reviewing motivation-related models.